DEVELOPING COMMUNICATIVE LANGUAGE TESTS FOR SENIOR HIGH SCHOOL - Y. M. Harsono (TEFLIN, 2005)
The Communicative Approach of teaching English in senior high school in Indonesia has been adopted since the implementation of The 1984 Curriculum, but the testsÃ¢â¬âthe communicative language testsÃ¢â¬â(CL Tests) have not been developed and used properly. The objective of the study is to develop CL Tests for senior high school. The procedure of conducting the study consists of three major steps, that is, identifying the objectives, developing the test specification, and developing the CL Tests. The development of the CL Tests in detail consists of fifteen sub-steps from determining what language skills tested, selecting the suitable source materials, up to rewriting the CL Tests to be used as CL Tests alternative for senior high school. The results of the test development reveal that there are fifteen CL Tests consisting of three tests of listening, three reading, three speaking, and three writing tests. The whole tests have construct and content validity, no complete evidence of concurrent validity with report marks and semester test scores, high to very high inter-rater reliability, and no complete practicality.